2002
DOI: 10.1042/cs103s302s
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 acts as a survival factor in ovarian carcinoma cells

Abstract: The aim of this study was to evaluate the role of endothelin-1 (ET-1) in the sensitivity of ovarian carcinoma to paclitaxel, one of the most common drugs used for the management of this tumour histotype. ET-1 is a powerful mitogenic peptide produced by ovarian carcinomas and it acts as an autocrine growth factor, selectively through ET(A) receptor (ET(A)R), which is predominantly expressed in this tumour. OVCA 433 and HEY, two ovarian carcinoma cell lines, which produce elevated amounts of ET-1 and express abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 15 publications
2
25
0
1
Order By: Relevance
“…Furthermore, it has been reported that ET-1 induces cell proliferation or antiapoptosis, via ET A R in NHEK, prostate and ovarian cancer cells, via ET B R in endothelial and melanoma, and via either receptor in colon cancer cells. 17,24,[27][28][29][30][31][32][33][34] In oral SCC cells, our results show that ET-1 can act via ET A R and/or ET B R for cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been reported that ET-1 induces cell proliferation or antiapoptosis, via ET A R in NHEK, prostate and ovarian cancer cells, via ET B R in endothelial and melanoma, and via either receptor in colon cancer cells. 17,24,[27][28][29][30][31][32][33][34] In oral SCC cells, our results show that ET-1 can act via ET A R and/or ET B R for cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] It has been suggested that ET-1 aids tumour growth and the progression of various tumours by either promoting cell proliferation or by protecting cells from apoptosis. 27,[29][30][31][32][33][34] Cell proliferation and apoptosis must be balanced to maintain tissue homeostasis. However, cancer cells are often characterized by increased resistance to apoptosis, which enables their survival under abnormal growth stimulation and mediates their increased resistance to various forms of cellular stress, such as DNA damage, hypoxia or nutrient deprivation.…”
mentioning
confidence: 99%
“…ET-1 has been repeatedly shown to mediate survival and/or proliferation in cell-based assays, including prostate cancer cells. 13,[20][21][22] ET-1 has been shown to have direct angiogenic activity on cultured endothelial cells which enhanced the effect of vascular endothelial growth factor (VEGF) and is mediated primarily by ETB. 23,24 In vivo studies have yielded conflicting results, with ET-1 failing to induce angiogenesis in chick embryo chorioallantoic membrane and rat sponge models and inducing angiogenesis, via ETA, in a rat cornea model and, when combined with VEGF, in the matrigel plug and chick embryo chorioallantoic membrane assays.…”
Section: Resultsmentioning
confidence: 99%
“…In ovarian cancer, endothelin-1 (ET-1) plays a key role in the development and progression of this tumor, promoting tumor cell proliferation (14,15), apoptosis protection (16), invasiveness (17), and neovascularization (18 -21). ET-1 and its selective receptor ET A (ET A R) are overexpressed in primary and metastatic ovarian carcinoma as compared with normal ovarian tissue (22).…”
Section: Cyclooxygenase (Cox)mentioning
confidence: 99%